The Effect of “Aware” Health Education on Knowledge of Early Detection of Breast Cancer in Adolescent Women in Health Center Area Lut Bargain in 2020 - rosmani sinaga (Institute of Computer Science (IOCS), 2022)
Breast cancer is one of the most common types of cancer in women. Breast cancer is a malignant tumor that grows in the breast tissue. Every year more than 185,000 women are diagnosed with breast cancer. The incidence of this disease is increasing in developed countries. Around 43,500 deaths from breast cancer each year make this disease the second leading cause of death after lung cancer in women. To find out the effect of carrying out breast self-examination (BSE) on students' knowledge in early detection of breast cancer. This type of research is a quantitative research with a research design using Quasi-Experimental. The instrument used for knowledge is a questionnaire while for the ability to use an observation sheet. The sampling technique in this study was using Porposive Sampling with a sample size of 68 people. Data processing using Wilcoxon statistical test. The results showed that most of the respondents after being given health education had a good level of knowledge about BSE, namely 62 people (91.2%). While the level of knowledge about BSE that is sufficient is 6 people (8.8%). From the results of statistical tests of knowledge and abilities before and after health education, the value of p = 0.000 (p <0.05). It can be concluded that there is an effect of health education on breast self-examination (BSE) on the knowledge of young women in an effort to detect breast cancer early in the Lut Tawar Health Center area. It is hoped that the Puskesmas will always carry out socialization about women's health and cooperate with health workers, especially regarding BSE examinations.